Theoretical aspects of competitiveness in construction enterprises - Lielgaidina, Laura; Geipele, Ineta (Business, Management and Economics Engineering, 2011)
In this paper, the authors present a short review of statistics in European counstruction market and describe literature on management in construction – concept and definitions of competitiveness, including PARTS checklist and Project Values, and suggestions for successful marketing as well. The enhancement of the competitiveness of construction enterprises is one of the most important strategic objectives in the construction industry. The company’s loss of competitiveness is its greatest threat. The focus of this paper is on improving quality and safety in construction enterprises – the research was done in order to obtain more information about quality performance measures used by building materials producers in Latvia. At the end of this paper, the authors shortly describe the results of the research.